Face validity of a dyslexia screening instrument for secondary students - Nik Zatul-Iffah N. Mohd Nabil; Mohd Effendi Ewan Mohd Matore; Mohd Syazwan Zainal (PLoS ONE, 2026)
Dyslexia is a specific learning difficulty marked by persistent challenges in reading accuracy, fluency, and word recognition despite adequate intelligence and instruction. In secondary schools, many cases remain unidentified due to the absence of screening instruments designed for older students. Early identification is essential for timely intervention, which requires valid and reliable tools. This study evaluated the face validity of a newly developed dyslexia screening instrument for secondary students through expert and test-taker assessments. The 28-item instrument, which focused on cognitive manifestations of dyslexia, was reviewed by ten experts and ten students. Items were rated on a 4-point Likert scale assessing clarity and comprehensibility, with analyses conducted using the Item-Level Face Validity Index (I-FVI), Scale-Level Face Validity Index by Average Agreement (S-FVI/AVE), and Scale-Level Face Validity Index by Universal Agreement (S-FVI/UA). Expert evaluation demonstrated that 85.7% of items achieved full agreement (I-FVI = 1.00), while scale-level indices exceeded recommended benchmarks (S-FVI/AVE = 0.96; S-FVI/UA = 0.86). Student evaluation also yielded high scale-level agreement (S-FVI/AVE = 0.92; S-FVI/UA = 0.82). A small number of items required linguistic refinement. Consequently, the findings indicate high agreement on the instrument’s clarity, comprehensibility, and acceptability, supporting face validity as a preliminary validation step for subsequent psychometric validation.